Sosialisasi dan Implementasi Media Ular Tangga Biologi Matematika untuk Meningkatkan Pembelajaran Aktif SMA Kristen Payeti - Ariesta Riupassa, Desly; Dunga Rima, Kornelia; Arinita Ina Kii, Rosalia; Tamu Ina, Susanti; Tamaela, Kevin (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
Low student engagement and activeness in the learning process is often caused by less interactive learning media. This community service activity aims to implement the "Snakes and Ladders in Biology and Mathematics" media as an effort to improve active learning and student conceptual understanding at Payeti Christian High School. The implementation method is carried out through three stages: preparation, socialization/simulation of media use, and impact evaluation. This media is a modification of a classic game integrated with biology and mathematics content in the form of challenges and assignments on each game square. The results of the activity show that the use of this media is able to create an active, fun, and positive competitive learning atmosphere for students. The implementation of this media can be an alternative for teachers in creating active and innovative game-based learning.